DEVELOPMENT DIRECTIONS OF THE LIFE INSURANCE SECTOR (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article outlines the economic essence and significance of life insurance, analyzes the current state and trends in the life insurance sector within the insurance market of Uzbekistan, and explores the directions for the development of thissector.